Formation of ITB in the vicinity of rational surfaces in the Uragan-3M torsatron - Volkov, E.D.; Berezhnyj, V.L.; Bondarenko, V.N.; Chechkin, V.V.; Fomin, I.P.; Grigor’eva, L.I.; Konovalov, V.G.; Kotsubanov, V.D.; Kulaga, A.E.; Lapshin, V.I.; Lesnyakov, G.G.; Litvinov, A.P.; et al. (Вопросы атомной науки и техники, 2003)
It was shown that there is the possibility of ITB formation in the vicinity of rational surfaces in a torsatron magnetic configuration. The formation of ITB is accompanied by fast change of plasma poloidal rotation velocity, radial electric field and its shear and the decrease of plasma density fluctuations. After the ITB formation the transition to the improved plasma confinement takes place. The transition stars when electron temperature in the region of rational surfaces is sufficient to satisfy the condition υTe/uei>>2πR0 (here υTe is electron thermal velocity and uei is the frequency of ion – electron collisions, and R0 is the major radius of the torus). Such a regime can be maintained during the whole duration of RF discharge without any disturbances. Показано, що існує можливість формування внутрішнього теплового бар’єру (ВТБ) в плазмі ВЧ розряду в околиці раціональних поверхонь в торсатронній магнітній конфігурації. Формування ВТБ супроводжується бистрими змінами швидкості полоідального обертання плазми, радіального електричного поля и його шира і зменшенням флуктуацій густини плазми поблизу раціональних поверхонь. Після формування ВТБ спостерігається перехід в режим поліпшеного утримання плазми. Час переходу зменшується із збільшенням ВЧ потужності нагріву. Показано, что имеется возможность формирования внутреннего теплового барьера (ВТБ) в плазме ВЧ разряда в окрестности рациональных поверхностей в торсатронной магнитной конфигурации. Формирование ВТБ сопровождается быстрыми изменениями скорости полоидального вращения плазмы, радиального электрического поля и его шира и уменьшением флуктуаций плотности плазмы вблизи рациональных поверхностей. После формирования ВТБ наблюдается переход в режим улучшенного удержания плазмы. Время перехода сокращается с увеличением ВЧ мощности нагрева.